Further knowledge of the genus Nyctobrya Boursin, 1957 from the Canary Islands (Spain), with description of a new species from El Hierro (Lepidoptera: Noctuidae) - Per Falck (SHILAP)
It describes Nyctobrya ingridae Falck, sp. nov. and record N. canaria (Alphéraky, 1890) for the first time from the Canary Island, El Hierro, Spain. Photographs of adults and genitalia of the new species are provided. Both species are DNA barcoded. Both morphology and analyses of DNA barcodes support the identification and distinctiveness of the new species as it appears well-supported and genetically isolated.